To Assess the Effectiveness of Structured Teaching Program on Nosocomial Infection and Its Prevention Among Staff Nurses Working in Shri J.G. Co-Operative Hospital Society, Ghataprabha, Karnataka - Mounesh; I. Clement (International Journal of Evidence Based Nursing And Practices, 2023)
Aims: To evaluate staff nurses’ knowledge of nosocomial infections. To examine the impact of a systematic teaching curriculum on staff nurses’ ability to avoid nosocomial infections. Furthermore, to ascertain the relationship between staff nurse pre-test knowledge and specific demographic factors. Methods: In order to investigate and evaluate the staff nurses’ level of knowledge regarding nosocomial infection prevention, an evaluatory research approach was used for this study. Pre-experimental design was determined to be appropriate given the nature of the topic being studied and the study’s goals to achieve. The convenient sampling method was used. The present study was conducted among staff nurses working in the Shri. J. G. Co-operative Hospital Society, Ghataprabha. The sample size consists of 25 staff nurses, structured knowledge questionaries are used to assess the knowledge level of staff nurses, descriptive and inferential statistics were used for the Data Analysis Interpretation. Results: The findings related to post-test mean knowledge score of staff nurses and GNM internship students were 20.16 with mean percentage of 80.64% and SD 5.29. In pre-test only 1(4%) of the respondents possess poor level of knowledge and remaining 18(72%) of the respondent possess average knowledge and 6(24%) good knowledge, respectively. in post-test, 10(40%) of the respondents possess average level knowledge and remaining 14(56%) of the respondents possess good and poor present of the had 1(4%) of the poor knowledge. It reveals that the post-test mean percentage knowledge score (mean percentage 80.64% and SD = 5.29) was found higher than pre-test mean percentage knowledge score (mean percentage = 65.76% and SD = 5.27). Statistical pair “t” test results with a paired “t” test value of 2.634 indicate that the difference between the pre-test and post-test value was judged to be statistically highly significant at the 0.05 level of significant (p). This demonstrates an improvement in knowledge score that is statistically significant and reflects the beneficial effects of a structured education strategy. Conclusion: The study was concluded that in pre-test 18 (72%) of the respondent possess average knowledge and in post-test 14 (56%) the respondents possess good knowledge. It was discovered that there was a statistically significant difference between the pre-test and post-test value. Consequently, the findings above show that a structured education program was successful in raising staff nurses’ knowledge of nosocomial infection prevention, and it was determined to be appropriate, successful, and able to inspire staff nurses to increase their knowledge.
Keywords: Nosocomial infection; evaluate; planned teaching program; prevention; staff nurses